Análisis del impacto en las exportaciones e importaciones en relación a las medidas Fito- Sanitarias del Instituto Colombiano Agropecuario (ICA) y su conexión en apertura y cierre de mercados. (2025)
The analysis of the impact of phytosanitary measures from the Colombian Agricultural Institute (ICA) on Colombia's agricultural exports and imports reveals that, while these regulations are essential for ensuring the safety of products and facilitating access to high-value international markets, they also present significant challenges, especially for small and medium producers due to high costs and the complexity of procedures. Compliance with these norms can open new commercial opportunities and improve the reputation of Colombian products, but the lack of adequate infrastructure and limited access to technology are barriers that hinder competitiveness. It is recommended to strengthen the ICA's infrastructure and promote public-private collaboration to optimize processes and support producers in complying with phytosanitary regulations.